Sustaining Competitive Advantage of Koperasi Kerajaan Tempatan towards the Economic Growth and Social Development of Local Authority - Azih, Muda (2023)
The abstract for the thesis titled "Sustaining Competitive Advantage of KOSPETA Towards the Economic Growth and Social Development of Local Authority" suffers from several issues that hinder its clarity and conciseness. This revised abstract aims to address these concerns by providing a more focused and informative summary of the research. This study explores strategies and practices employed by KOSPETA to maintain its competitive advantage and their impact on local economic growth and social development. Through a thorough examination of KOSPETA's intricate operations and its interactions with the local community, this research seeks to uncover the key drivers of sustained competitive advantage. The objectives of the study are to identify the best practices adopted by KOSPETA, assess their effectiveness, and analyze their implications for the broader community. To achieve this, a comprehensive analysis of KOSPETA's strategies and practices, including its supply chain management, marketing techniques, and community engagement, was conducted. The findings reveal that KOSPETA's commitment to environmentally sustainable practices and its active involvement in local capacity building initiatives are instrumental in fostering economic growth and social development. Furthermore, this study recognizes the importance of acknowledging its limitations, particularly in terms of the generalizability of the findings to other contexts and the potential biases in data collection. In conclusion, this research contributes to our understanding of how businesses like KOSPETA can play a pivotal role in local economic growth and social development. It underscores the significance of sustainable and community-oriented business practices in achieving these goals. The implications of this study suggest that other businesses and local authorities can benefit from adopting similar strategies to create a more prosperous and inclusive society.